Caracterização do uso e ocupação do solo e qualidade da água com utilização das técnicas de geoprocessamento. - Wrublack, Suzana Costa (2012)
the interest of many researchers who have studied the characteristics and environmental realities of agriculture in order to improve its sustainable development. Thus, this trial aimed at characterizing the use and occupation of soil and water quality according to the GIS techniques. Physical parameters as turbidity, temperature were analyzed as well as chemical ones: pH, electrical conductivity, bicarbonate, chloride, phosphate and nitrate and biological parameters as thermotolerant coliform in two annual distinct raining periods (1 and 2). Based on field surveys, by georeferencing of sampling points, farms perimeters and survey data concerning soil use and occupation, some information was recorded on water quality for irrigation and the area management, especially the permanent preservation areas. Google Earth program provided the images used to map soil use and occupation. The determination of influence areas was obtained according to Thiessen polygons technique. The data obtained from the mapping of soil use as well as water quality for irrigation in periods 1 and 2 were statistically analyzed by techniques of Principal Component Analysis, Detrended Correspondence Analysis and Canonical Correspondence Analysis to record the relation of soil use and occupation on water quality. The interpretation of satellite imagery from Google Earth with ArcGIS 9.3 software allowed a map drawing regarding soil use and occupation in four categories: areas with temporary crops, permanent crops, urban areas and forests. Thiessen polygons technique allowed the recognition of influence areas on each point of irrigation water catchment and identification of soil use categories in representing polygons of the points where there were restrictions to use irrigation water according to phosphate and thermotolerant coliform parameters. The Principal Component Analysis of chemical, physical and biological parameters data of water explained 53.27% variation of water quality among the sampled properties. Among the analyzed parameters, it was observed that nitrate, thermotolerant coliform, temperature, electrical conductivity and bicarbonate were the ones that best explained the spatial variation of water quality, with the highest correlations with the major axis. The relation among soil use and occupation and water quality parameters by canonical correspondence analysis identified two significant axes of variation in order to explain variation in water quality. In the first axis, the highest values of electrical conductivity, nitrate, bicarbonate and phosphate were identified in period 2 and period 1 as well as variables as temperature and thermotolerant coliform. The second axis was positively related to the permanent preservation areas and reforestation, with some positive influence on turbidity and electrical conductivity. The restriction on irrigation water use based on parameters as phosphate and thermotolerant coliform was associated to the development of agricultural activities.